Description of Physical Activities in the Elderly with Hypertension in Posbindu Sumber Sehat, Demak Regency - Soesanto, Edy; Khoiriyah, Khoiriyah; Handayani, Ike Fitri (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Degenerative processes in the elderly can cause various kinds of disorders, including cardiovascular disorders such as hypertension. The heart muscle loses contractile efficiency and strength, decreases relaxation of vascular smooth muscle, loss of connective tissue elasticity resulting in decreased ability to stretch, and decreases the ability of blood vessels to stand up. Physical activity can have an impact on changes in the strength of the smooth muscle in the heart so that the pulse in the heart can be strong and regular. AIM: The purpose of this study was to determine the description of the elderly physical activity level with hypertension in Posbindu Sumber Sehat Kangkung Village, Demak Regency. METHODS: This type of research is descriptive using a cross-sectional design. The study was conducted in Posbindu Sumber Sehat Kangkung Village, Demak Regency, with a proportional stratified random sampling technique. The number of samples in this study was 63 elderly with hypertension respondents. The data collection tool uses the Global Physical Activity Questionnaire. Analysis of the data used frequency distribution. RESULTS: The results showed that the elderly physical activity with hypertension was included in the category of moderate physical activity (60.3%); blood pressure in elderly with hypertension was mostly included in the category of mild hypertension (54.0%). CONCLUSION: Based on these results, it is expected that elderly with hypertension will always increase physical activity, especially the frequency and duration that is carried out according to ability.